The Balance 2∙f (O) – f (H) as a Cornerstone in Formulation of Electrolytic Systems - M. Michałowska-Kaczmarczyk Anna; Michałowski Tadeusz (Journal of New Developments in Chemistry, 2018)
The Generalized Electron Balance (GEB) concept, related to electrolytic redox systems, is considered according to principles of Generalized Approach to Electrolytic Systems (GATES). Two equivalent Approaches (I and II) to GEB are presented. The Approach I, when perceived in convention of the card game, is based on the common pool of electrons as money, introduced by electron-active elements, named as players; electron-non-active elements are called there as fans. The GEB obtained according to Approach II results from the linear combination f12 = 2∙f(O) – f(H) of elemental balances: f1 = f(H) for H, and f2 = f(O) for O. Very important properties of f12 are presented here in details, and illustrated by a redox system where comproportion- ation reactions occur
Keywords: Thermodynamics